(untitled) (Journal of Informatics Education and Research, 2024)
The study explores the depiction of assault against women within the framework of profoundly ingrained beliefs, cultural standards, and traditions as represented in Etaf Rum’s novel "A Woman is No Man." The story depicts the obstacles experienced by three generations of Palestinian women who reside in America. The study adopts a multidisciplinary approach, relying on gender studies, anthropology of culture, and postcolonial literary ideas. The research investigates characters’ which attempts to navigate the complicated convergence of ethnicity, household responsibility, and personal autonomy via detailed observation of character interactions, conversations, and narrative developments. The study shed light on the resilience and agency displayed by the female characters as they address the oppressive forces that seek to enclose them as well as demonstrate the complex relationship among cultural mores as well as the perpetuation of violence against women through examining the nuanced nuances of Rum’s storytelling. The study contributes to the wider discussion on gender, culture, and domestic abuse by highlighting the importance of nuanced and culturally sensitive treatments to meet the particular issues encountered by women in societies where traditional values collide with current reality.